Social Media Content Creation Training with Artificial Intelligence for Branding and Promotion of Micro, Small and Medium Enterprises Banyuwangi: Pelatihan Pembuatan Konten Media Sosial dengan Artificial Intelligence untuk Branding dan Promosi UMKM Banyuwangi - Indah Werdiningsih; Endah Purwanti; Nania Nuzulita (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Most of Micro, Small and Medium Enterprises (MSMEs) in Banyuwangi promote their products only by participating in events such as exhibitions, held in Banyuwangi. MSMEs do not have branding for their products, or the branding is not attractive enough.  Therefore, MSMEs in Banyuwangi need effective promotion and branding. Community service activities by the Information Systems Study Program, Faculty of Science and Technology, Airlangga University, aim to provide training on creating social media content by utilizing Artificial Intelligence (AI) for branding and promoting MSMEs in Banyuwangi. The applications used in this activity are Instagram, Facebook, Canva, and ChatGPT. There are three stages of activities, namely preparation, implementation, and evaluation. Twenty-one (21) Banyuwangi MSMEs, 14 lecturers, and 3 students attended the community service activities. MSMEs participating in this community service have various products, such as food, drinks, furniture, and handicrafts. After implementation, participants were asked to fill out a questionnaire to get an overview of their understanding after being given the training. The evaluation was carried out using a Likert scale. Sixteen (16) indicators were used to evaluate this activity.  The evaluation results show an average score of 97.48%.  This score proves that this community service activity is very suitable for increasing the ability to create branding and promotions for MSMEs in Banyuwangi. The training participants were enthusiastic about understanding and creating effective promotional digital content.